Parkinsonian Rigidity Shows Variable Properties Depending on the Elbow Joint Angle - Takuyuki Endo; Toshimitsu Hamasaki; Ryuhei Okuno; Masaru Yokoe; Harutoshi Fujimura; Kenzo Akazawa; Saburo Sakoda (Parkinson's Disease)
Parkinsonian rigidity has been thought to be constant through a full range of joint angle. The aim of this study was to perform a detailed investigation of joint angle dependency of rigidity. We first measured muscle tone at the elbow joint in 20 healthy subjects and demonstrated that an angle of approximately 60° of flexion marks the division of two different angle-torque characteristics. Then, we measured muscle tone at the elbow joint in 24 Parkinson’s Disease (PD) patients and calculated elastic coefficients in flexion and extension in the ranges of 10°–60° (distal) and 60°–110° (proximal). Rigidity as represented by the elastic coefficient in the distal phase of elbow joint extension was best correlated with the UPDRS rigidity score (r=0.77). A significant difference between the UPDRS rigidity score 0 group and 1 group was observed in the elastic coefficient in the distal phase of extension (P<0.0001), whereas no significant difference was observed in the proximal phase of extension and in each phase of flexion. Parkinsonian rigidity shows variable properties depending on the elbow joint angle, and it is clearly detected at the distal phase of elbow extension.